Abundance and movement of fishes among nearshore habitat types in small boreal shield lakes - Graham R. Mushet; Caleb Yee; Scott Bergson; Paul J. Blanchfield (Hydrobiologia, 2023)

Behavioural responses of a cold-water benthivore to loss of oxythermal habitat - Tazi H. Rodrigues; Andrew J. Chapelsky; Lee E. Hrenchuk; Graham R. Mushet; Lauren J. Chapman; Paul J. Blanchfield (Environmental Biology of Fishes, 2022)
Climate-driven declines in oxythermal habitat in freshwater lakes can impose prolonged constraints on cold-water fishes sensitive to hypoxia. How fish cope with severe habitat limitations is not well understood, yet has implications for their persistence. Here, we use acoustic-positioning telemetry to assess seasonal habitat occupancy and activity patterns of lake whitefish ( Coregonus clupeaformis ), a cold-water benthivore, in a small boreal lake that regularly faces severe oxythermal constraints during summer stratification. During this stratified period, they rarely (< 15% of detections) occupied depths with water temperatures > 10 °C (interquartile range = 5.3–7.9 °C), which resulted in extensive use (> 90% of detections) of water with < 4 mg L −1 dissolved oxygen (DO; interquartile range = 0.3–5.3 mg L −1 ). Lake whitefish were least active in winter and spring, but much more active in summer, when only a small portion of the lake (1–10%) contained optimal oxythermal habitat (< 10 °C and > 4 mg L −1 DO), showing frequent vertical forays into low DO environments concurrent with extensive lateral movement (7649 m d −1 ). High rates of lateral movement (8392 m d −1 ) persisted in the complete absence of optimal oxythermal habitat, but without high rates of vertical forays. We found evidence that lake whitefish are more tolerant of hypoxia (< 2 mg L −1 ) than previously understood, with some individuals routinely occupying hypoxic habitat in winter (up to 93% of detections) despite the availability of higher DO habitat. The changes in movement patterns across the gradient of habitat availability indicate that the behavioural responses of lake whitefish to unfavourable conditions may lead to changes in foraging efficiency and exposure to physiological stress, with detrimental effects on their persistence.

Evidence for temporally coherent increases in the abundance of small Discostella (Bacillariophyceae) species over the past 200 years among boreal lakes from the Experimental Lakes Area (Canada) - Brendan Wiltse; Graham R. Mushet; Andrew M. Paterson; Brian F. Cumming (Journal of Paleolimnology, 2022)

Heterogeneous response of diatom assemblages since ca. 1945 in lakes from boreal regions of northern Alberta and Saskatchewan, Canada - Kathleen R. Laird; Graham R. Mushet; Roger J. Flower; Alexander P. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2020)

Bottom-Up Forces Drive Increases in the Abundance of Large Daphnids in Four Small Lakes Stocked with Rainbow Trout (Oncorhynchus mykiss), Interior British Columbia, Canada - Graham R. Mushet; Kathleen R. Laird; Peter R. Leavitt; Stephen Maricle; Andrew Klassen; Brian F. Cumming (Ecosystems, 2020)
The introduction of salmonids into lakes of western North America for sport fishing is a widespread phenomenon. While numerous investigations have documented cascading trophic interactions upon the introduction of fish into naturally fishless systems, little research has been done to investigate the importance of natural fish status (fishless vs. fish bearing) in modulating historical food web response to dual forcing by bottom-up (resource regulation from nutrients) and top-down (planktivory from stocked fish) processes. We used the paleolimnological record to reconstruct food web changes in four lakes in interior British Columbia that have been stocked with rainbow trout since the early to mid-1900s. Analysis of pigments, diatoms, and Cladocera was undertaken in cores from all lakes. We predicted that if fish were important in structuring cladoceran abundance and composition, we would document a decline in the abundance of large daphnids post-stocking in our two naturally fishless lakes, and little change in the two fish-bearing lakes. Instead, we documented increased abundance of large daphnids after stocking in all lakes in the early to mid-1900s, a finding inconsistent with size-selective predation from planktivorous fish. Further, our data suggest that deep, low-oxygen refugia may be important in sustaining populations of large Daphnia , a process which was enhanced by increased nutrients and lake production according to sub-fossil diatom and pigment analyses. This study shows that fish stocking does not invariably result in a decrease in large-bodied Cladocera and that nutrients and lake type can modulate the response of invertebrate planktivores.

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)